Full characterization and transcript expression profiling of the interferon regulatory factor (IRF) gene family in Atlantic cod (Gadus morhua). (September 2019) - Inkpen, Sabrina M.; Solbakken, Monica H.; Jentoft, Sissel; Eslamloo, Khalil; Rise, Matthew L.
Abstract: Atlantic cod ( Gadus morhua ) represents a unique immune system among teleost fish, making it a species of interest for immunological studies, and especially for investigating the evolutionary history of immune gene families. The interferon regulatory factor (IRF) gene family encodes transcription factors which function in the interferon pathway, but also in areas including leukocyte differentiation, cell growth, autoimmunity, and development. We previously characterized several IRF family members in Atlantic cod ( Irf4a, Irf4b, Irf7, Irf8, and two Irf10 splice variants) at the cDNA and putative amino acid levels, and in the current study we took advantage of the new and improved Atlantic cod genome assembly in combination with rapid amplification of cDNA ends (RACE) to characterize the remaining family members (i.e. Irf3, Irf5, Irf6, Irf9, and two Irf2 splice variants). Real-time quantitative PCR (QPCR) was used to investigate constitutive expression of all IRF transcripts during embryonic development, suggesting several putative maternal transcripts, and potential stage-specific roles. QPCR studies also showed 11 of 13 transcripts were responsive to stimulation with poly(I:C), while 6 of 13 transcripts were responsive to lipopolysaccharide (LPS) in Atlantic cod head kidney macrophages, indicating roles for cod IRF family members in both antiviral and antibacterial responses. This study is the first to investigate expression of the complete IRF family in Atlantic cod, and suggests potential novel roles for several of these transcription factors within immunity as well as in early development of this species. Highlights: Characterization of the Atlantic cod IRF family has now been completed at mRNA level. Expression during early development suggests additional roles of IRFs. Most IRF transcripts respond to antiviral and/or antibacterial pathway stimulation. Several cod IRFs likely function in both antiviral and antibacterial responses.